2021
DOI: 10.1021/acssuschemeng.1c00059
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Fuel Cells with a Plasma-Etched Polymer Electrolyte Membrane with Microhole Arrays

Abstract: Interface engineering based on the design and fabrication of micro/nanostructures has received much attention as an effective way to improve the performance of polymer electrolyte membrane (PEM) fuel cells while using the same materials and quantity. Herein, we fabricated spatially hole-array patterned PEMs with different hole depths using both the plasma etching process and a polymeric stencil with 40 μm-sized apertures. This novel technological approach exhibited high pattern fidelity over a large area and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Furthermore, from the measured mechanical properties of the membrane (Figure S6), the reference and C-HC show similar ultimate tensile strengths, Young’s modulus, and elongation at the break. However, the MC-HC showed a little decrease in elongation at the break due to the stress concentration effect at the edges of the microsized structures. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, from the measured mechanical properties of the membrane (Figure S6), the reference and C-HC show similar ultimate tensile strengths, Young’s modulus, and elongation at the break. However, the MC-HC showed a little decrease in elongation at the break due to the stress concentration effect at the edges of the microsized structures. …”
Section: Resultsmentioning
confidence: 99%
“…Studies on diverse microelectromechanical systems (a technique for securing the precise design and reproducibility of the surface structure) have endeavored to fabricate nanoscale/ macroscale pattern structures on the electrolyte membrane surface. [80][81][82] In the initial stages of these studies, direct patterning of the membrane using electron beam (e-beam) lithography was implemented. [83] Omosebi et al [84] reported that e-beam lithography coupled with a dry etching method could fabricate a well-ordered micro-hole array (2 µm in diameter and 5 µm in pitch size).…”
Section: Single-scale Patterned Membranesmentioning
confidence: 99%
“…By using a so-lithographic method, membranes with isoporous and various pore sizes/thicknesses can be made easily at a low cost in a short time. 22,23 Since the membrane is ultra-thin (<120 mm in this study) and exible, it is spaceefficient and easy to integrate even into the curved system, which paves the way for customization of the design, size, and construction of the water-owing systems. To show the advantages and usefulness of the OGIM based water owing system, ne-tuned liquid ow systems with OGIM have been demonstrated in this study.…”
Section: Introductionmentioning
confidence: 99%